Creating a musical for pre-schoolers in South Africa as pedagogical praxis for a tertiary music education module. Issue 1 (6th March 2023) - van Vreden, Mignon
Abstract: Despite a renewed interest in educational practices to develop future music educators in South Africa for a rapidly changing professional landscape, little is known about the meaning students themselves ascribe to these practices towards their own development as music educators. This instrumental case study investigated the learning experiences of second-year BMus students creating a musical for pre-schoolers. Data were collected through interviews, observations and reflective journals. Six themes emerged through a thematic analysis of student experiences, namely interaction, preparation, skills development, stagecraft, performance and enjoyment. A conceptual model that explains the production of a musical as a pedagogical praxis connects these themes with existing literature on three teaching and learning approaches that framed the study, namely authentic arts-based pedagogy, project-based learning and community of practice.